Activation of the classical complement pathway in spontaneous bacterial peritonitis. Issue 3 (March 1992) - Bird, G; Senaldi, G; Panos, M; Rolando, N; Alexander, G; Vergani, D; Williams, R
Abstract : To investigate the possibility that low complement concentrations in the plasma and ascites of patients with severe liver disease could be secondary to complement consumption, complement activation was studied in 32 patients with severe liver disease, 11 of whom had spontaneous bacterial peritonitis (SBP). In patients with SBP, plasma C3 and C4 were significantly lower than in uninfected patients (mean values 0.74 v 1.13 g/l, p less than 0.01 and 0.20 v 0.28 g/l, p less than 0.05 respectively). Plasma complement activation via the classical pathway, as shown by C4d/C4, was significantly increased in patients with SBP compared with uninfected patients (37.3 v 22.2, p less than 0.01) as was C3d/C3 (14.0 v 8.11, p less than 0.01), but there was no significant difference in Ba/B between SBP and uninfected patients. Ascitic C3 concentrations were higher in patients without SBP than in infected patients (0.37 v 0.08 g/l, p less than 0.05), as were factor B values (0.11 v 0.03 g/l, p less than 0.05). There was no significant difference in ascitic C4 concentrations in patients with SBP compared with uninfected patients (0.03 v 0.07 g/l). Although consumption of C3, as shown by C3d/C3 in ascites, was increased in infected patients compared with uninfected patients (79.1 v 36.1, p less than 0.05), there was no difference in ascitic complement activation between the groups for either the classical or alternative pathways. In SBP, decreased plasma C3 and C4 are primarily caused by increased activation of the classical pathway and not impaired hepatic synthesis. Activation and consumption of C3 is one factor causing the low ascitic C3 concentrations observed in SBP.